2010
DOI: 10.1002/arch.20397
|View full text |Cite
|
Sign up to set email alerts
|

The importance of exportin and Ran for nucleocytoplasmic shuttling of the ecdysteroid receptor

Abstract: Nuclear localization of the ecdysteroid receptor (EcR) is increased in HeLa cells if exportin-1 (CRM1), a predominant carrier for export of proteins and RNA from the nucleus into the cytoplasm, is knocked down by siRNA against exportin. However, knockdown of the small G protein Ran, which is essential for nuclear transport, leads to an arrest of EcR in the cytoplasm, but does not prevent efficient nuclear import of the most important heterodimerization partner of EcR, ultraspiracle (Usp). Like in vertebrate ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…Therefore, we infer that the daily nucleocytoplasmic shuttling of EcR that occurs during defined periods of larval–adult development of Rhodnius employs cytoskeletal tracks for movement. Nucleocytoplasmic shuttling of EcR is further supported by the fact that EcRs in other species possess several nuclear export signals in addition to a nuclear import signal (Gwózdz et al, 2007; Betanska et al, 2011). Because the nuclear EcR rhythm is synchronous to the robust circadian rhythm of circulating ecdysteroids it is inferred that Rhodnius cells detect and respond to the daily signals in the rhythmic ecdysteroid titer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we infer that the daily nucleocytoplasmic shuttling of EcR that occurs during defined periods of larval–adult development of Rhodnius employs cytoskeletal tracks for movement. Nucleocytoplasmic shuttling of EcR is further supported by the fact that EcRs in other species possess several nuclear export signals in addition to a nuclear import signal (Gwózdz et al, 2007; Betanska et al, 2011). Because the nuclear EcR rhythm is synchronous to the robust circadian rhythm of circulating ecdysteroids it is inferred that Rhodnius cells detect and respond to the daily signals in the rhythmic ecdysteroid titer.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, steroid receptors and most of the nuclear factors involved in signaling cascades are continually shuttling between the nucleus and the cytoplasm (review by Echeverria and Picard, 2010). EcR possesses both nuclear localization and nuclear export signals (Gwózdz et al, 2007) and interacts with exportin 1 (Betanska et al, 2011). The presence of cytoplasmic EcR in insects has been noted but no significance has been attributed to it (Lammerding-Köppel et al, 1998; Gwózdz et al, 2007; Nieva et al, 2007; Betanska et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current studies have not yet clarify whether the TOR pathway mediates the Rho1 effect on egg development and production in wasps. However, it has been shown that knockdown of Ras superfamily member, Ran causes ecdysteroid receptor arrest in the cytoplasm (He et al, 2010;Betanska et al, 2011) or downregulation of genes responsible for ecdysteroid biosynthesis (Liu et al, 2021). This study, measured ecdysteroid titers in females and observed that MmRho1 knockdown significantly increased (Fig.…”
Section: Discussionmentioning
confidence: 73%
“…, 2010; Betanska et al. , 2011) or downregulation of genes responsible for ecdysteroid biosynthesis (Liu et al. , 2021).…”
Section: Discussionmentioning
confidence: 99%